What Are the Most Effective Neighborhood Ranges for Social Comparison to Improve Water Use Efficiency? - Otaki, Yurina; Honda, Hidehito; Ueda, Kazuhiro (Frontiers in Water, 2022)
It is commonly recognized in the field of water demand management that social comparison of water usage among people with a similar background is an effective measure to promote water efficiency. Many studies have used “neighborhood” to represent group similarity, but it is unclear how much geographic proximity is appropriate for defining a neighborhood. Therefore, the aim of this study is to clarify what neighborhood range is the most effective for promoting residential water use efficiency. We conducted a field experiment on social comparison feedback using two neighborhood ranges: narrow (condominium complex level) and wide (prefecture level), and analyzed changes in the water usage of 114 households residing in a condominium in the Tokyo metropolitan area, based on daily household water consumption data and an emoticon-based feedback system. As a result of classification of water consumption trend patterns using the K-means clustering method, it was suggested that those with low-consumption reduced their consumption as a result of the intervention, irrespective of neighborhood range. Despite the limited amount of data, the results provide insights into designing and implementing more effective feedback methods outside the US and European regions, especially in the context of residential water efficiency.